Does learning a second or third language affect the adaptation of cognitive control in multilinguals? A longitudinal fMRI study - Zehui Xing; Xiyuan Wang; Junjun Huang; John W. Schwieter; Huanhuan Liu (Cognitive Neurodynamics, 2026)

A dual brain EEG examination of the effects of direct and vicarious rewards on bilingual Language control - Junjun Huang; Shuang Liu; Mengjie Lv; John W. Schwieter; Huanhuan Liu (Cognitive Neurodynamics, 2026)

Enriching triboelectric signal characteristic toward vibration waveform recognition by electron-beam irradiation - Hu Bian; Fanzheng Zeng; Haoran Yu; Xingyi Song; Jia Liu; Xingke Zhao; Zhenming Chen; Chengmei Gui; Junjun Huang (Chemical Engineering Journal, 2026)

Fusicoccane glycosides from the endophytic fungus Talaromyces sp. DC-26 - Peng Zhou; Jingwen Yu; Xueying Deng; Jinyan Cai; Wenya Feng; Junjun Liu; Qin Li; Chong Dai; Chunmei Chen; Yonghui Zhang; Hucheng Zhu (Phytochemistry, 2026)

Model test study on hydro-mechanical behaviour of dredged sludge treated with lime and prefabricated horizontal drains under vacuum preloading - Guizhong Xu; Yanlin Wei; Huan Dong; Junjun Ni; Chao Liu (Ocean Engineering, 2026)

Electrospun chitosan/PCL/Tween-80 nanofibers incorporated with Ocimum basilicum essential oil as bio-based active packaging materials - Qi Liu; Shuqing Wang; Junjun Liang; Hong Chen; Sheng Jiang; Lin Tang (Food Bioscience, 2026)

An all-in-one endoluminal acoustofluidic system enables spatiotemporal transmucosal drug delivery and barrier repair for inflammatory bowel disease - Yichen Liu; Xiaoming Zheng; Yang Qin; Jing Han; Zhiwei Cong; Shu Fan; Yan Li; Ruochen Wang; Xiaolong Guo; Qichao Huang; Xunan Jing; Yibo Liu; et al. (Chemical Engineering Journal, 2026)

Nanoconfinement-enhanced peroxymonosulfate activation by Co single atoms in hollow mesoporous carbon: Roles of active-site chemistry and mesoscale confinement - Hao Luo; Junli Zheng; Jiaxin Liu; Junjun Ma; Rui He; Chuqi Huang; Rong Xie; Qintie Lin (Water Research, 2026)

Engineered norfloxacin-derived carbonized polymer dots for synergistic antibacterial and anti-inflammatory periodontitis therapy - Xinyu Jiang; Yu Deng; Jia Liu; Huan Chen; Hongyan Lin; Yu Zhong; Junjun Liu; Xinchan Liu; Bai Yang (Chemical Engineering Journal, 2026)

Feasibility evaluation for cockroach from Periplaneta americana as a new protein feed ingredient in pigs - Zilin Li; Yu Cao; Meng Liu; Jingru Yuan; Jia Li; Wentao Huo; Mingyi Huang; Shuaishuai Kang; Shiyan Sui; Xiaokang Ma; Yujun Wu; Dandan Han; et al. (Animal Feed Science and Technology, 2026)

Deep-Water Seafloor Undulations Related to Bottom Currents: A Case Study from the Shenhu Canyon Area, Northern South China Sea - Junjun Zhang; Xishuang Li; Xiaoqing Xu; Lejun Liu; Qingjie Zhou (Journal of Marine Science and Engineering, 2026)
Bottom currents and their associated sedimentary structures are key agents in shaping deep-sea morphodynamics, among which the genesis of seafloor undulations is still debated, restricting engineering risk assessment and resource development safety. Based on high-resolution multibeam bathymetry, sub-bottom profiles, and near-bottom current observations, this study analyzes morphological characteristics, internal reflection structures, and near-bottom current dynamic processes of seafloor undulations in the Shenhu canyon area. The results indicate that undulations occur at canyon heads, canyon interfluve, and east side of canyon. The undulations are generally characterized by vertical aggradation, with some sediment waves exhibiting directional crestline migration accompanied by wave merging, indicating the existence of persistent sediment transport processes. Within the canyon, the flow is concentrated and exhibits significant vertical deflection, reflecting the pronounced flow-guiding effect of the confined topography on near-bottom currents, which consequently controls the lateral migration of crestlines on both sides of the canyon and the shaping of seafloor undulations at canyon heads by internal tides. In contrast, in the relatively open canyon interfluve, flow directions are more dispersed, predominantly characterized by weaker currents. These findings contribute to the understanding of deep-water sedimentary dynamic processes and provide a reference for interpreting the genesis of similar deep-water seafloor undulations.

Heterogeneous Response and Zonal Micromechanical Deterioration of Deep Rock-forming Minerals Under Laser Irradiation - Yuanru Li; Mingzhong Gao; Xuemin Zhou; Yanbo Bai; Junjun Liu; Lei Yang; Haichun Hao; Bengao Yang; Jing Xie; Zheng Gao (Rock Mechanics and Rock Engineering, 2026)

Divergent responses of soil methane uptake to nitrogen addition across upland ecosystems - Xinya Sui; Hong Zhang; Yunyi Xie; Yaqi Liu; Xiaoli Cheng; Guihua Liu; Junjun Wu (Soil and Tillage Research, 2026)

Influence of biochar with varied pyrolysis temperatures on soil desiccation cracking under dry-wet cycles - Siqing Yang; Junjun Ni; Yifei Liu; Hamed Sadeghi (Bulletin of Engineering Geology and the Environment, 2026)

Integrated chemometrics and untargeted metabolomics reveal the differential effects of drying methods on the quality of Sharen (Amomum villosum Lour.) - Zhixia Sun; Jun Chen; Junjun He; Ivan Shorstkii; Liqing Du; Taotao Dai; Yihui Wang; Yanli Yao; Chengmei Liu; Lizhen Deng (Food Bioscience, 2026)

Enzymatically synthesized native-like guaiacyl dehydrogenation polymer as a formaldehyde-free adhesive for high-strength, water-resistant plywood - Rui Luo; Wenhao Liu; Qian Tu; Yuanpu Wang; Junjun Chen; Junxian Xie; Rong Zhang; Nianjie Feng; Peng Wang (Chemical Engineering Journal, 2026)

Insights into chloride-induced calcium-magnesium hydrates formation in alkali-activated marine soft clay - Quanyi Zhang; Zhengjian Liu; Junjun Ni; Qiang Guo; Yuchen Wang (Journal of Soils and Sediments, 2026)

Highly cross-linked carbon nanotubes co-doped with bimetallic Mo-W carbide and cobalt nanoparticles as a high-performance bioanode for microbial fuel cells - Zhenghui Qiu; Jiaxuan Liu; Junjun Xu; Dongsheng Zhao; Guanglong Zhang; Kangnan Liu; Yue Zhao; Jiyong Zheng; Jinwei Zhang; Cunguo Lin (Journal of Environmental Chemical Engineering, 2026)

Low-frequency vibration-induced crack expansion: Insights from resonance frequency and amplitude effects - Junjun Feng; Ting Zhang; Wangyuan Liu; Xinyu Zhang; Yankun Ma; Xiaofei Liu (Gas Science and Engineering, 2026)

Performance evaluation and mechanism analysis of different ice particle distribution shape parameter schemes in BCC-AGCM - Pengcheng Lin; Chunsong Lu; Yiming Liu; Xin He; Junjun Li; Tongwen Wu; Yixiong Lu (Atmospheric Research, 2026)

Influence of calcium-based localized flocculation near drainage body on dredged sludge consolidation under vacuum preloading - Jun Chen; Xingbing Li; Junjun Ni; Guizhong Xu; Chao Liu (Marine Georesources & Geotechnology, 2026)

Plantaricin-producing Lactiplantibacillus plantarum NDF28B2 as an adjunct culture enhances fermented Milk texture and suppresses Listeria monocytogenes - Nan Xiao; Yang Liu; Chengcheng Zhang; Chuan Zhang; Pan Huang; Gang Wang; Shumao Cui; Wenwei Lu; Bo Yang; Junjun Wu; Xiaomei Lyu; Fengwei Tian; et al. (Food Research International, 2026)

A critical review of phase change material–aerogel flexible composite films for personal thermal management: performance, mechanism, and applications - Xianfei Liu; Hui Wang; Hui Zhang; Fang Wang; Mengjie Li; Bo Wen; Junjun Li; Caixia Zhu (Energy and Buildings, 2026)

Fabrication of extracorporeal mechanical energy harvesting and implantable triboelectric nanogenerators for self-powered medical devices - Zhenni Liu; Hu Bian; Cong Lin; Quan Chen; Jia Liu; Zhenming Chen; Jun Chen; Dongdong Fang; Junjun Huang (Chemical Engineering Journal, 2026)

Mechanisms of Drillability Enhancement and Damage Evolution in Granite Under Coupled Laser-Drill Interaction - Lei Yang; Mingzhong Gao; Bengao Yang; Jing Xie; Zhiqiang He; Junjun Liu; Fei Li; Xuemin Zhou; Kunchen He (Rock Mechanics and Rock Engineering, 2026)

A soybean EIN transcription factor confers resistance to Phytophthora sojae and favorable agronomic traits - Meng Liu; Jiaxin Yin; Xudong Wei; Junjun Song; Yaqun Dongye; Xi Chen; Xin Fang; Xinyue Yu; Yan Sun; Jihao Ju; Xiaoyu Chen; Junjiang Wu; et al. (Plant Cell Reports, 2026)

Design, mechanical model, and seismic performance of a novel variable-stiffness SMA damper - Qiang Lian; Huihui Yuan; Weidong Zhuo; Junjun Guo; Maide Liu (Soil Dynamics and Earthquake Engineering, 2026)

From single-interface LN2 fracturing to CBM stimulation: Temperature optimization and cracking mechanism - Junjun Feng; Hongqing Qiu; Peng Zhang; Wei Li; Xiaofei Liu; Yankun Ma (Fuel, 2026)

Effects of multi-source solid waste-based stabilizing materials on the improvement of high-salinity silt - Yongsheng Yao; Chen Liu; Yuchen Wang; Xiyan Chen; Jue Li; Junjun Ni (Transportation Geotechnics, 2026)

Coupled tectonic-climatic-oceanographic dynamics drove the evolution of foraminiferal diversity in South China during the Middle to Late Mississippian - Chao Liu; Junjun Qi; Pedro Cózar; Ismael Coronado; Fei Li; Weiqing Liu; Meng Li; Ping Wang; Xin Li; Xia Hu; Song Jin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mechanical and fracture behavior of red sandstone under confining pressure and laser irradiation using CT scanning and uniaxial compression - Xuemin Zhou; Haichun Hao; Lei Yang; Junjun Liu; Jing Xie; Yuanru Li; Lang Zhou; Jiahua Li; Mingzhong Gao (International Journal of Rock Mechanics and Mining Sciences, 2026)

A new and simple hypoplastic model for saturated soils reinforced by plant roots - Shusen Liu; Junjun Ni; Xudong Zhao; Yufeng Gao; Ning He; Yongfeng Deng (Computers and Geotechnics, 2026)

Parallel finite element forward modeling of 3-D magnetotelluric conductivity and permeability anisotropy with coupled PML boundary conditions - Shuaiying Qiao; Tiaojie Xiao; Junjun Zhou; Chunye Gong; Bo Yang; Jie Liu; Yun Wang; Qinglin Wang (Computers & Geosciences, 2026)

Role of flow electrode chamber channel depth in charge transfer and ion migration in FCDI: Mechanistic insights and energy efficiency evaluation - Cheng Wang; Jianrui Niu; Situ Mu; Yongkun Shi; Jing Zhang; Chun Liu; Junjun Ma (Chemical Engineering Journal, 2026)

Enhanced osteogenic differentiation of rBMSCs under low-frequency dynamic stimulation of piezoelectric membranes - Jing Liu; Donglin Li; Xiaoqing Liu; Jiahao Zeng; Yuxuan Lu; Weiqiang Fan; Shuncheng Zhang; Yuxuan Jia; Linxuan Zheng; Xin Chen; Hongzhang Deng; Yongmei Wang; et al. (Chemical Engineering Journal, 2026)

Bayesian-informed DNN and ensemble learning for predicting soil water characteristic curves from easily measurable parameters - Yifei Liu; Junjun Ni; Fei Zhang; Ekaterina Kravchenko; Viroon Kamchoom (Transportation Geotechnics, 2026)

L-amino acids modulate biofilm formation, UV resistance, and insecticidal activity in Bacillus thuringiensis formulations: Mechanisms and optimization - Zixuan Wang; Yimeng Zhang; Junjun Chen; Qingqing Liu; Xueqin Luo; Qiuting Xu; Hongxin Su; Yanyan He; Fang Xiong; Shuang Lin; Tianpei Huang; Xiong Guan (Pesticide Biochemistry and Physiology, 2026)

Reconciling Jupiter’s vertical motions with the observed cloud structure in the upper troposphere - João M. Mendonça; Tapio Schneider; Junjun Liu; Yuan Lian (Icarus, 2026)

Redox electrolyte enhances dual-anode FCDI (DA-FCDI) desalination of brackish and synchronously removal NOM - Kexin Kang; Situ Mu; Jianrui Niu; Yongkun Shi; Jing Zhang; Chun Liu; Junjun Ma (Chemical Engineering Journal, 2026)

Environmental impact and carbon footprint analysis of rural domestic wastewater treatment plants based on life cycle assessment method: A case study of Fuzhou City, China - Hanwei Huang; Xiaoying Lin; Junjun Chen; Xueping Liu; Zushan Zhuo; Yuqi Li (Journal of Water Process Engineering, 2025)

Elucidating the mechanism of sulfur reactions over NiFe2O4 oxygen carrier at atomic level - Cheng Shen; Yu Li; Daifen Chen; Xin Liu; Junjun Sun; Jintian He; Laihong Shen (Fuel, 2025)

Separation and detection of ginsenosides: Challenges, industrial implications, and developments - Anqi Liu; Junjun Zhou; Yiling Luo; Yingbo Li; Yu Yang; Zibo Meng; Lixia Zhou; Hanlei Zhang; Na Liu; Ming Hui; Dandan Zhai; Peng Li (Food Research International, 2025)

Experimental and DEM investigation of root orientation effects on shear behavior of soils subjected to freeze–thaw cycles - Junjun Ni; Haoyu Zhang; Shusen Liu; Yongfeng Deng; Ning He (Engineering Geology, 2025)

Effect of straw-based vertical drains on consolidation of dredged sediment under intermittent vacuum preloading - Junjun Ni; Shusen Liu; Mengying Gao; Qiyuan Han; Jiaxing Weng; Dan Zhang (Journal of Soils and Sediments, 2025)

Investigating the variations in microbiome and volatilome characteristics of sauce-flavor Muqu across different grades and production rounds - Yu Mu; Linpei Liu; Junjun He; Hong Zhang; Shirui Yu; Zhiyu Zhu; Ying Huang; Mingyue Mou; Chunlin Zhang (Food Chemistry, 2025)

The effects of dietary astaxanthin on the intestinal microbiota and metabolites, antioxidant capacity, and resistance to Decapod iridescent virus 1 in Macrobrachium rosenbergii - Cui Liu; Qiusheng Jing; Li Wang; Qincheng Huang; Yukun Jie; Yutong Zheng; Tiantian Ye; Junjun Yan; Zhimin Gu (Fish & Shellfish Immunology, 2025)

Mechanism and Feasibility Evaluation of Laser-Assisted Rock-Breaking in Drilling Fluid Environment - Xuemin Zhou; Mingzhong Gao; Junjun Liu; Lei Yang; Haichun Hao; Bengao Yang; Zhiqiang He; Xuan Wang (Rock Mechanics and Rock Engineering, 2025)

Coupling renewable energy with urban greening: quantifying the sustainable development potential of photovoltaic-green roofs - Taoyu Chen; Yantong Li; Yi Zhang; Hexu Ji; Xinyu Wang; Junjun He; Qunyue Liu; He Zhang (Sustainable Cities and Society, 2025)

Experimental and simulation study of volatile organic compounds adsorption over natural Opoka based zeolite 13X - Yangyu Liu; Chenxi Zhang; Arman Peyravi; Lei Jiang; Zaher Hashisho; Linghe Cheng; Hailong Zhang; Zhongzheng Yang; Junjun Wang; Jiuyue Wang; Yuping Tong (Chemical Engineering Journal, 2025)

High chemodiversity of nitrogen-containing organic compounds in vehicle emissions driven by transformative reactions - Shuang Chen; Yisheng Xu; Dandan Liu; Junjun Deng; Rui Liu; Shaofei Kong; Pingqing Fu (Journal of Hazardous Materials, 2025)

Polyphenol-based coacervate droplets as building blocks for protocells and prototissues - Qi Xie; Wei Chen; Zijian Huang; Yuan Gao; Haoyu Zhang; Zhanhao Zhou; Samira Batur; Chuansheng Fu; Jiao Zhang; Conglian Yang; Junjun Liu; Li Kong; et al. (Chemical Engineering Journal, 2025)

Hotspot regions of reactive oxygen species production and their environmental impacts in periodically flooded soil environments: A review - Xing Liu; Yvjie Xie; Paul N. Williams; Baoying Wang; Haiyi Chen; Xiaotong Li; Li Zhang; Leyi Wang; Junjun Liu; Yingxin Wu; Jun Luo (Critical Reviews in Environmental Science and Technology, 2025)

Resistance reduction method for building transmission and distribution systems based on an improved random forest model: A tee case study - Ao Tian; Wanqing Zhang; Junjun Hei; Yao Hua; Xiaozhi Liu; Jianxun Wang; Ran Gao (Building and Environment, 2025)

Influence of plant root aging on water percolation in three earthen landfill cover systems: A numerical study - Jingsong Zhou; Junjun Ni; Shusen Liu; Yuchen Wang; Clarence E. Choi (Journal of Hydrology, 2025)

Influence of soil crack on large-deformation consolidation of dredged clay under vacuum preloading: A numerical solution - Guizhong Xu; Yifei Liu; Junjun Ni; Yupeng Cao; Sifang Deng (Computers and Geotechnics, 2025)

Evolutionary repeatability of chromatin accessibility in the hippocampus between echolocating bats and soft-furred tree mice - Luye Shi; Yuanshuo Ma; Qinyang Hua; Junjun Hao; Qin Zhang; Yaxin Ye; Lu Yang; Qi Liu; Peng Chen; Zhen Liu; Peng Shi (Science China Life Sciences, 2025)

Shear strength of biopolymer amended soil under freeze-thaw cycles: Experimental investigation and DEM modeling - Jiayu Gu; Junjun Ni; Shusen Liu; Yanbo Chen (Engineering Geology, 2025)

Genetic identification and characterization of quantitative trait loci for wheat grain size-related traits independent of grain number per spike - Tao Li; Yanyan Tang; ZhengXi Lin; Jinghui Wang; Juanyu Zhang; Qiang Li; Furong Huang; Junjun Liang; Haili Zhang; Zehou Liu; Jun Li; Wuyun Yang; et al. (Theoretical and Applied Genetics, 2025)

Selective gold extraction from e-waste leachate via sulfur-redox mechanisms using sulfhydryl-functionalized MOFs - Jialong Qin; Hengzhi Liu; Zhuoya Fang; Junjun Pei; Kai Yin; Kaixing Fu; Jinming Luo (Water Research, 2025)

Sustainable Fe(II) oxidation/reduction and release/recovery dual cycle in a multi-chamber Fe(III)/Peroxymonosulfate electrochemical system: Application, mechanism, and optimization - Minghao Yu; Meng Chen; Chenxu Yang; Jianrui Niu; Jing Zhang; Situ Mu; Ruina Zhang; Junjun Ma; Chun Liu (Chemical Engineering Journal, 2025)

Data-Driven Carbon Emission Dynamics Under Ship In-Port Congestion - Weiyu Liu; Bowei Xu; Junjun Li (Journal of Marine Science and Engineering, 2025)
Berthing operation heterogeneity across ship types causes significant uncertainty in assessing port congestion and carbon emissions over comparable timeframes. This study quantifies in-port emission dynamics for four cargo ship types (container, liquid bulk, dry bulk, and general cargo) using an operational phase-specific emission accounting model. We propose a hybrid deep learning model that integrates Two-Dimensional Convolutional Neural Networks (2DCNN) with Squeeze-and-Excitation Attention Mechanisms (SEAM) and Bidirectional Long Short-Term Memory Networks (BiLSTM) layers, optimized via the Triangulation Topology Aggregation Optimizer (TTAO) for hyperparameter tuning. Empirical analysis at Ningbo Zhoushan Port shows that liquid bulk carriers emit 23–41% more than other ship types due to extended auxiliary engine/boiler use during cargo handling. The 2DCNN-SEAM model significantly improves BiLSTM prediction accuracy—reducing Mean Absolute Percentage Error (MAPE) by 18.7% and increasing the R2 value to 0.94—by effectively capturing spatiotemporal congestion features. Results confirm that operational congestion is a critical emission multiplier, especially for ships requiring prolonged auxiliary system use during berthing. These insights inform targeted decarbonization strategies for port authorities, prioritizing operational efficiency and energy transition for high-emission ship categories.

Alzheimer’s Disease-Derived Outer Membrane Vesicles Exacerbate Cognitive Dysfunction, Modulate the Gut Microbiome, and Increase Neuroinflammation and Amyloid-β Production - Shouchao Wei; Xiaochen Ma; Yating Chen; Junjun Wang; Li Hu; Zhou Liu; Lang Mo; Ning Zhou; Wenrong Chen; He Zhu; Shian Yan (Molecular Neurobiology, 2025)

Mixed vineyard prunings and sheep manure compost: Creating changes in vineyard soil dominant microbiota to impact fruit quality - Qian Tu; Yuanyuan Li; Weikang Ding; Shubo Zhou; Yanping Huang; Shiqiu Liu; Xuwu Min; Jiarui Zhang; Junjun Li; Chunlong Yuan (Applied Soil Ecology, 2025)

Prescribed performance rapid attitude maneuvering control based on time delay estimation for flexible spacecraft system with input deadzone - Junjun Liu; Yufu Cui; Haoping Wang; Xingyu Zhou; Linghui Yu (Advances in Space Research, 2025)

Hydroxysafflower yellow A alleviates the inflammatory response in astrocytes following cerebral ischemia by inhibiting the LCN2/STAT3 feedback loop - Lijuan Song; Yige Wu; Lijun Yin; Yanzhe Duan; Jianlin Hua; Mengwei Rong; Kexin Liu; Junjun Yin; Dong Ma; Ce Zhang; Baoguo Xiao; Cungen Ma (Metabolic Brain Disease, 2025)

Optimization Strategy for Container Transshipment Between Yards at U-Shaped Sea-Rail Intermodal Terminal - Zeyi Liu; Junjun Li (Journal of Marine Science and Engineering, 2025)
The U-shaped automated container terminal (U-ACT) meets the requirements of sea-rail intermodal transportation with its unique layout. However, this layout also presents challenges, such as complex container transshipment planning and challenging equipment scheduling, which limit further improvements in overall efficiency. This paper focuses on the integrated scheduling of horizontal transportation and container-handling equipment for container transshipment at U-ACT. To minimize operation time and energy consumption while addressing path conflicts among container trucks, we designed a two-layer scheduling model to generate an optimal scheduling scheme for each automated device. Given the complexity of the problem, we developed a reinforcement learning-driven hyper-heuristic algorithm (RLHA) capable of efficiently searching for near-optimal solutions. Small-scale experiments demonstrate that our RLHA outperforms other algorithms, improving optimization results by 5.14% to 28.87% when the number of container operation tasks reaches 100. Finally, large-scale experiments were conducted to analyze key factors impacting sea-rail intermodal transport operations at U-ACT, providing a foundation for practical optimization.

Incartrilactones A and B: Two schinortriterpenoids with a 14,15-seco-15,17-cyclolancifoartane skeleton from Schisandra incarnata - Ying Gao; Juan Chen; Junjun Liu; Zijian Huang; Xiaogang Peng; Wanpeng Li; Chunlun Qin; Hanli Ruan (Phytochemistry, 2025)

Self-Assembled Arachidonic Acid Nanomicelles for Radiation-Induced Ferroptosis to Enhance Tumor Radioimmunotherapy - Jiadong Wang; Yueyue Jing; Li Liu; Pengfei Xing; Zheng Deng; Yifan Zhang; Xirui Wu; Bin Hu; Cai Zhang; Xianglong Sun; Yuqian Liu; Jiawei Liu; et al. (Chemical Engineering Journal, 2025)

Hydration and solution properties of fluorescently labeled wheat arabinoxylans following enzymatic hydrolysis - Jieya Wang; Yan Liu; Qingbin Guo; Junjun Li; Liang Zou; Xinzhong Hu (Food Hydrocolloids, 2025)

Identification and validation of a novel nine-gene prognostic signature of stem cell characteristic in hepatocellular carcinoma - Yahang An; Weifeng Liu; Yanhui Yang; Zhijie Chu; Junjun Sun (Journal of Applied Genetics, 2025)

Insights from Computational Fluid Dynamics and In Vitro Studies for Stent Protrusion in Iliac Vein: How Far Shall We Go? - Zhenmin Fan; Jian Lu; Hao Cheng; Xia Ye; Xiaoyan Deng; Pengfei Zhao; Junjun Liu; Mingyuan Liu (Cardiovascular Engineering and Technology, 2025)

Selenium Counteracts Tight Junction Disruption and Attenuates the NF-κB-Mediated Inflammatory Response in Staphylococcus aureus-Infected Mouse Mammary Glands - Junjun Liu; Juan Wang; Shiyang XV; Chongliang Bi (Biological Trace Element Research, 2025)

Ecosystem-atmosphere exchange of methane in global upland and wetland ecosystems - Junjun Wu; Hong Zhang; Xiaoli Cheng; Guihua Liu (Agricultural and Forest Meteorology, 2025)

Bromodomain and extraterminal domain (BET) promote autophagy in buffalo sertoli cells - Yuan Yang; Junjun Zhang; Yue Zhang; Qinqiang Sun; Ruixin Liu; Chunrong Xu; Peng Xu; Yangqing Lu; Qiang Fu (Theriogenology, 2025)

Cerebrospinal Fluid-Derived extracellular Vesicle-Inspired Multifunctional bone regeneration scaffold for cranial defect repair - Jie He; Yifan Zhang; Xiaolan Sun; Minjie Wang; Qing Zhang; Simin Liu; Shaojie Yu; Xuan Wang; Zhenxing Wang; Junjun Li; Xiaobin Jiang (Chemical Engineering Journal, 2025)

Unveiling the role of intrinsic defects in N/S Co-Doped hard carbon for superior sodium-ion batteries - Yunlei Yang; Chang Liu; Junjun Yao; Zhenqi Tang; Ying Sun; Kun Zhang; Hui Li; Tianyi Ma; Jieshan Qiu (Chemical Engineering Journal, 2025)

The coupling model of random forest and interpretable method quantifies the response relationship between PM2.5 and influencing factors - Jinxing Liu; Hui Yu; Yaqing Zhang; Junjun Chen; Shiyuan Feng; Rui Guo; Feng Wang; Bo Xu; Guoliang Shi; Yinchang Feng (Atmospheric Environment, 2025)

Multidimensional effects of arable soil organic carbon distribution: a comparison among terrains - Huarong Tan; Fengman Fang; Yuesheng Lin; Junjun Zhi; Youru Yao; Yangbing Liu; Wangbing Liu; Lei Jin; Jin Wang (Journal of Soils and Sediments, 2025)

Influence of biopolymer-vegetation interaction on soil hydro-mechanical properties under climate change: A review - Yifei Liu; Junjun Ni; Jiayu Gu; Shusen Liu; Yi Huang; Hamed Sadeghi (Science of The Total Environment, 2024)

Hydrodynamic characteristics and internal flow field of a perforated fishing vessel under wave conditions - Xi Zhang; Junjun Lv; Dachuan He; Ke Wang; Ying Liu; Jie Zhi (Ocean Engineering, 2024)

Amylopectin from maize-derived carbonized polymer dots as a novel high-efficiency antioxidant for periodontitis treatment - Junjun Liu; Naibo Feng; Xinyu Jiang; Xirui Xin; Yubo Hou; Zhende Jiang; Laijin Lu; Weixian Yu; Bai Yang (Chemical Engineering Journal, 2024)

Highly efficient adventitious root regeneration and Agrobacterium rhizogenes-mediated hairy root transformation in pear - Cheng Xue; Liyan Chang; Junjun Liu; Kaidi Gu; Pengfei Zheng; Jun Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Macrophage migration inhibitory factor reversed senescent phenotype in human chondrocytes in vitro - Zhenlan Fu; Qingqing Li; Peiyao Jiang; Xiongbo Song; Junjun Yang; Guangxing Chen; Xiaoyuan Gong; Liu Yang (Molecular Biology Reports, 2024)

Deformation characteristics of root-reinforced soil under traffic induced cyclic loading - Shusen Liu; Jun Li; Shumin Lyu; Yi Fang; Xiaodong JI; Junjun Ni (Transportation Geotechnics, 2024)

Triboelectric signal enhancement via interface structural design and integrated with deep learning for real-time online material recognition - Cheng Shen; Jingyi Chen; Yue Liu; Zhenming Chen; Junjun Huang (Chemical Engineering Journal, 2024)

Abnormal percent amplitude of fluctuation in patients with lifelong premature ejaculation is associated with neurotransmitter profiles - Jiarui Yuan; Pinxiao Wang; Dingxin Nie; Wanxiang Zheng; Kepu Liu; Jianyong Feng; Yuntao Zhang; Yanzhu Wang; Junjun Gao; Ming Gao (Brain Imaging and Behavior, 2024)

Three-Dimensional Marine Magnetotelluric Parallel Forward Modeling in Conductive and Magnetic Anisotropic Medium Using Finite-Element Method Based on Secondary Field - Zongyi Zhou; Tiaojie Xiao; Junjun Zhou; Xiaoxiong Zhu; Bo Yang; Chunye Gong; Jie Liu; Yun Wang (Journal of Marine Science and Engineering, 2024)
The marine magnetotelluric (MMT) method is a significant tool extensively utilized in offshore studies, including the understanding of the Earth’s tectonics and hydrocarbon exploration. Conductive anisotropy and non-zero magnetic susceptibility are common phenomena observed in the Earth’s subsurface, and MMT forward modeling is the basis of practical inversion. However, numerical modeling that incorporates both conductive anisotropy and magnetic susceptibility has received limited attention. Moreover, both accuracy and efficiency are crucial in developing a 3D MMT modeling algorithm. Therefore, we developed a multi-level parallel MMT forward modeling algorithm that is capable of simultaneously modeling conductive and magnetic arbitrary anisotropic models using the vector finite element method based on the secondary field formula. The algorithm’s accuracy was validated through comparisons with previously published results for an arbitrary anisotropic model. The results show that the maximum relative error is below 2%, and the speedup reaches an impressive value of 552.41 when running with 2048 cores. Furthermore, the MMT responses of conductive anisotropy and magnetic susceptibility were comprehensively analyzed by several typical models. Our findings highlight the importance of considering magnetic susceptibility in magnetite-rich regions, particularly as the MMT responses may exhibit opposite responses for anomalies with lower resistivity and higher magnetic susceptibility compared with the surrounding rocks.

Compositions and sources of fluorescent water-soluble and water-insoluble organic aerosols - Hao Ma; Dandan Liu; Junjun Deng; Jiaming Zhao; Qiang Zhang; Zhimin Zhang; Wei Hu; Libin Wu; Pingqing Fu (Science of The Total Environment, 2024)

N-doped carbon achieved by pyrolyzing urea and active carbon for the capacitive deionization coupled PMS oxidation system - Meng Chen; Chenxu Yang; Minghao Yu; Mengyao Han; Zihan Meng; Tian Zhao; Jianrui Niu; Situ Mu; Jing Zhang; Junjun Ma; Chun Liu (Desalination, 2024)

Temperature and plant root effects on soil hydrological response and slope stability - Junjun Ni; Shusen Liu; Yi Huang; Yufeng Gao (Computers and Geotechnics, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

Hydro-mechanical behaviour of straw fiber-reinforced cemented dredged sediment at high water content - Guizhong Xu; Yifei Liu; Junjun Ni; Yuchen Wang (Journal of Soils and Sediments, 2024)

Soil methane uptake is tightly linked to carbon dioxide emission in global upland ecosystems - Junjun Wu; Long Chen; Hong Zhang; Xiaoxiang Zhao; Xiaoli Cheng; Kerong Zhang; Guihua Liu (Agriculture, Ecosystems & Environment, 2024)

Multi-chamber membrane capacitive deionization coupled with peroxymonosulfate to achieve simultaneous removal of tetracycline and peroxymonosulfate reaction byproducts - Minghao Yu; Chenxu Yang; Meng Chen; Yunke Li; Kexin Kang; Cheng Wang; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Journal of Hazardous Materials, 2024)

Optimization of the intermediate chamber improves desalination performance in flow electrode capacitive deionization (FCDI): A comparative study - Yunke Li; Chenxu Yang; Meng Chen; Yonghuan Bian; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Desalination, 2024)

Experimental and theoretical study on performance of Cu-Fe spinel supported with certain inerts during chemical looping combustion - Yu Li; Li Wang; Daifen Chen; Jing Liu; Wei Fan; Junjun Sun (Chemical Engineering Journal, 2024)

Integration of surface-based and space-based atmospheric CO2 measurements for improving carbon flux estimates using a new developed 3-GAS inversion model - Shu'an Liu; Xiaofeng Pan; Xiangyun Xiong; Tianle Sun; Lin Xue; Huifang Zhang; Junjun Fang; Jingchun Fang; Guchun Zhang; Hui Xu; Baozhang Chen (Atmospheric Research, 2024)

Blood–Brain Barrier Permeability is Affected by Changes in Tight Junction Protein Expression at High-Altitude Hypoxic Conditions—this may have Implications for Brain Drug Transport - Guiqin Liu; Qian Wang; Lu Tian; Mengyue Wang; Delong Duo; Yabin Duan; Yue Lin; Junjun Han; Qiangqiang Jia; Junbo Zhu; Xiangyang Li (The AAPS Journal, 2024)

Temperature sensitivity of aerobic and anaerobic organic carbon mineralization varies with climate and soil depth in riparian zones - Mingzhu Lu; Gang He; Lei Fan; Guihua Liu; Junjun Wu; Wenzhi Liu; Lin Ma (Soil Biology and Biochemistry, 2024)

Biological culture module for plant research from seed-to-seed on the Chinese Space Station - Chaoxian Jia; Weibo Zheng; Fangwu Liu; Kun Ding; Yongchun Yuan; Junjun Wang; Dazhao Xu; Tao Zhang; Huiqiong Zheng (Life Sciences in Space Research, 2024)

Large eddy simulation of turbulent non-premixed oxy-fuel jet flames with different Reynolds numbers - Junjun Guo; Xudong Jiang; Hong G. Im; Zhaohui Liu (Fuel, 2024)

Evaluation of biological activity and prebiotic properties of proanthocyanidins with different degrees of polymerization through simulated digestion and in vitro fermentation by human fecal microbiota - Xiaoyi Chen; Shuai Liu; Hong Song; Chunlong Yuan; Junjun Li (Food Chemistry, 2024)

Differential responses of temperature sensitivity of greenhouse gases emission to seasonal variations in plateau riparian zones - Yongtai Pan; Junjun Wu; Guihua Liu; Wenzhi Liu; Lin Ma (Environmental Pollution, 2024)

Effects of bed pumice content on lahar erosion: An example from Changbaishan volcano, China - Shengwu Qin; Jiangfeng Lv; Shuangshuang Qiao; Junjun Chen; Jingyu Yao; Feng Wan; Shuaiying Peng; Gohar Rehman; Xiaowei Liu (Engineering Geology, 2024)

Optimizing a Rock-Like Material Mix Design for Enhancing the Mining Fracture Monitoring Accuracy of Borehole Resistivity Method - Yuben Liu; Zhu Gao; Junjun Jiao; Mohammad Waqar Ali Asad; Michael Hitch; Danqi Li (Rock Mechanics and Rock Engineering, 2024)

Clusterin is a Potential Therapeutic Target in Alzheimer’s Disease - Nazhakaiti Palihati; Yuanhong Tang; Yajuan Yin; Ding Yu; Gang Liu; Zhenzhen Quan; Junjun Ni; Yan Yan; Hong Qing (Molecular Neurobiology, 2024)

Tree stem methane emissions: Global patterns and controlling factors - Junjun Wu; Hong Zhang; Xiaoli Cheng; Guihua Liu (Agricultural and Forest Meteorology, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Carbon felt (CF) acted as an “ionic capacitor” to enhance flow electrode capacitive deionization (FCDI) desalination performance - Yunke Li; Junjun Ma; Minghao Yu; Jianrui Niu; Jiarong Gu; Meng Chen; Puming Zhang; Jing Zhang; Chun Liu (Desalination, 2024)

The effect of land degradation and restoration on particulate and mineral-associated organic carbon - Hong Zhang; Guihua Liu; Junjun Wu (Applied Soil Ecology, 2024)

9,9′-epoxylignans from Syringa pinnatifolia: A typical case of stereochemical assignment by a quantum chemical calculation with MAEΔΔ parameter - Shungang Jiao; Changxin Liu; Panlong Chen; Junjun Li; Jingjing Sun; Xiaoli Gao; Xingyun Chai (Phytochemistry, 2024)

Chae-type cytochalasans from coculture of Aspergillus flavipes and Chaetomium globosum - Wenjing Wang; Junguo Huang; Liangxiu Liao; Xiaolong Yang; Chunmei Chen; Junjun Liu; Hucheng Zhu; Yonghui Zhang (Phytochemistry, 2024)

Numerical investigation on NO formation of staged oxy-fuel combustion in a 35 MW large pilot boiler - Junjun Guo; Teng Guo; Tai Zhang; Fan Hu; Pengfei Li; Zhaohui Liu (Fuel, 2024)

Integrated vegetation cover of typical steppe in China based on mixed decomposing derived from high resolution remote sensing data - Junjun Wu; Yi Li; Bo Zhong; Qinhuo Liu; Shanlong Wu; Changyuan Ji; Jing Zhao; Li Li; Xiaoliang Shi; Aixia Yang (Science of The Total Environment, 2023)

Small molecule linoleic acid inhibiting whey syneresis via interact with milk proteins in the fermentation of set yogurt fortified with c9,t11-conjugated linoleic acid - Junjun Qing; Cheng Peng; Hongbing Chen; Haixing Li; Xiaohua Liu (Food Chemistry, 2023)

Preparation of dual-functional packaging films containing green tea essential oil microcapsules for strawberry preservation: Excellent barrier properties and antioxidant activity - Weijie Zhao; Lianjun Yu; Yali Gu; Weijia Ma; Kehui Wang; Junjun Liang; Qi Liu (Food Bioscience, 2023)

First identification and molecular subtyping of Blastocystis in free-living wild birds from urban Xinxiang, China - Tiantian Li; Huimei Feng; Yingxu Zheng; Junjun Lv; Chi Zhang; Xuefeng Yang; Xuehan Liu (Veterinary Research Communications, 2023)

Potential role of selenium in alleviating obesity-related iron dyshomeostasis - Guanwen Liu; Junjun Li; Bing Pang; Yinghui Li; Fengqin Xu; Ning Liao; Dongyan Shao; Chunmei Jiang; Junling Shi (Critical Reviews in Food Science and Nutrition, 2023)

Gut microbiota bridges dietary nutrients and host immunity - Lijuan Fan; Yaoyao Xia; Youxia Wang; Dandan Han; Yanli Liu; Jiahuan Li; Jie Fu; Leli Wang; Zhending Gan; Bingnan Liu; Jian Fu; Congrui Zhu; et al. (Science China Life Sciences, 2023)

Spatial and molecular variations in forest topsoil dissolved organic matter as revealed by FT-ICR mass spectrometry - Ming Sheng; Shuang Chen; Cong-Qiang Liu; Qinglong Fu; Donghuan Zhang; Wei Hu; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (Science of The Total Environment, 2023)

Energy optimal depth control for multimodal underwater vehicles with a high accuracy buoyancy actuated system - Junjun Cao; Rui Lin; Chunhu Liu; Hao Feng; Caoyang Yu; Baoheng Yao; Lian Lian (Ocean Engineering, 2023)

Dynamic modeling and switching analysis of all-attitude multimode underwater vehicle for multidimensional data acquisition - Rui Lin; Junjun Cao; Jialuan Xiao; Caoyang Yu; Chunhu Liu; Baoheng Yao; Lian Lian (Ocean Engineering, 2023)

Alternate intercropping of cotton and peanut increases productivity by increasing canopy photosynthesis and nutrient uptake under the influence of rhizobacteria - Baojie Chi; Jin Liu; Jianlong Dai; Zhenhuai Li; Dongmei Zhang; Shizhen Xu; Junjun Nie; Sumei Wan; Cundong Li; Hezhong Dong (Field Crops Research, 2023)

Solution-catalyzed carbothermal reduction of argo-waste SiO2 enables low-temperature and fast synthesis of Si(Ⅱ)-C anode - Zi'ang Liu; Ruohan Yu; Shaohua Zhu; Jiashen Meng; Xuanpeng Wang; Chaojiang Niu; Lianmeng Cui; Fan Qiao; Junjun Wang; Liqiang Mai (Chemical Engineering Journal, 2023)

Highly sensitive, wide-pressure and low-frequency characterized pressure sensor based on piezoresistive-piezoelectric coupling effects in porous wood - Jingjing Luo; Feihua Liu; Ao Yin; Xue Qi; Jiang Liu; Zhongqi Ren; Shiqiang Zhou; Yuxin Wang; Yang Ye; Qingzhi Ma; Junjun Zhu; Kang Li; et al. (Carbohydrate Polymers, 2023)

Observational study of relationships between entrainment rate, homogeneity of mixing, and cloud droplet relative dispersion - Chunsong Lu; Lei Zhu; Yangang Liu; Fan Mei; Jerome D. Fast; Mikhail S. Pekour; Shi Luo; Xiaoqi Xu; Xin He; Junjun Li; Sinan Gao (Atmospheric Research, 2023)

Particulate organic carbon is more sensitive to nitrogen addition than mineral-associated organic carbon: A meta-analysis - Junjun Wu; Hong Zhang; Yongtai Pan; Xiaoli Cheng; Kerong Zhang; Guihua Liu (Soil and Tillage Research, 2023)

Nrf2 protects against renal fibrosis induced by chronic cadmium exposure in mice - Chengjie Chen; Zhengsheng Zhou; Siqi Yu; Yawei Ma; Gang Wang; Xue Han; Congcong Jiao; Junjun Luan; Zhiyuan Liu; Yuanyuan Xu; Huihui Wang; Qiang Zhang; et al. (Food and Chemical Toxicology, 2023)

Gut microbiota as a potential target for developing anti-fatigue foods - Yinghui Li; Junjun Li; Fengqin Xu; Guanwen Liu; Bing Pang; Ning Liao; Huixin Li; Junling Shi (Critical Reviews in Food Science and Nutrition, 2023)

Fluorescence Properties and Chemical Composition of Fine Particles in the Background Atmosphere of North China - Ping Li; Siyao Yue; Xiaoyang Yang; Di Liu; Qiang Zhang; Wei Hu; Shengjie Hou; Wanyu Zhao; Hong Ren; Gang Li; Yuanguan Gao; Junjun Deng; et al. (Advances in Atmospheric Sciences, 2023)

Covalent-crosslinking IRMOF-3-NH2/PVC ultrafiltration membrane for simultaneous removal of bisphenol A and Cd2+ ions in water - Yong Pan; Wei Huang; Yong Zhou; Feng Liu; Chen Zhu; HaiXia Pang; JunJun Tan; BaoMing Xu (Journal of Cleaner Production, 2023)

Synthesis of a micro-nano FeOx/MnOx modified large volume non-enamel ceramsites for selective and efficient adsorption of cadmium - Junkang Guo; Xianwei Yu; Muhammad Haris; Tian Liu; Jiayuan Wang; Junjun Zhao; Yifan Li; Chao Zhang (Journal of Environmental Chemical Engineering, 2023)

Multiple biological activities and biosynthesis mechanisms of specific conjugated linoleic acid isomers and analytical methods for prospective application - Suhong Li; Liangwei Xu; Junjun Qing; Xiaodan Wu; Haixing Li; Hongbing Chen; Xiaohua Liu (Food Chemistry, 2023)

Inversion of TEM measurement data via a quantum particle swarm optimization algorithm with the elite opposition-based learning strategy - Junjun Jiao; Jiulong Cheng; Yuben Liu; Haiyan Yang; Dingrui Tan; Peng Cheng; Yuqi Zhang; Chenglin Jiang; Zhi Chen (Computers & Geosciences, 2023)

Recombinant HBsAg-S and RFRP-3 DNA vaccine promotes reproduction hormone secretion in sheep - Yi Ding; Xunping Jiang; Haijing Jing; Guiqiong Liu; Junjun Cheng (Theriogenology, 2023)

Nitrogen addition stimulates litter decomposition rate: From the perspective of the combined effect of soil environment and litter quality - Junjun Wu; Hong Zhang; Xiaoli Cheng; Guihua Liu (Soil Biology and Biochemistry, 2023)

Tools for analyzing protonation states and for tracing proton transfer pathways with examples from the Rb. sphaeroides photosynthetic reaction centers - Rongmei Judy Wei; Umesh Khaniya; Junjun Mao; Jinchan Liu; Victor S. Batista; M. R. Gunner (Photosynthesis Research, 2023)

Enhanced VFAs production from microalgal hydrolytic acidification with ultrasonic-alkali pretreatment - Liwen Zhang; Jingjing Yang; Bingdang Wu; Junjun Liu; Xiaoyi Xu; Wei Wu; Jinlong Zhuang; Hanxiang Li; Tianyin Huang (Algal Research, 2023)

Resilience Regulation Strategy for Container Port Supply Chain under Disruptive Events - Bowei Xu; Weiting Liu; Junjun Li (Journal of Marine Science and Engineering, 2023)
There are many inevitable disruptive events, such as the COVID-19 pandemic, natural disasters and geopolitical conflicts, during the operation of the container port supply chain (CPSC). These events bring ship delays, port congestion and turnover inefficiency. In order to enhance the resilience of the CPSC, a modified two-stage CPSC system containing a container pretreatment system (CPS) and a container handling system (CHS) is built. A two-dimensional resilience index is designed to measure its affordability and recovery. An adaptive fuzzy double-feedback adjustment (AFDA) strategy is proposed to mitigate the disruptive effects and regulate its dynamicity. The AFDA strategy consists of the first-level fuzzy logic control system and the second-level adaptive fuzzy adjustment system. Simulations show the AFDA strategy outperforms the original system, PID, and two pipelines for improved dynamic response and augmented resilience. This study effectively supports the operations manager in determining the proper control policies and resilience management with respect to indeterminate container waiting delay and allocation delay due to disruptive effects.

Application of phosphorus amendments reduces metal uptake and increases yield of Oryza saliva L. (rice) in Cd/Cu-contaminated paddy field - Jiahui Wu; Qingmei Song; Yingxin Wu; Junjun Liu; Zhuohao Wu; Jingyan Zhou; Yuntao Wang; Wencheng Wu (Chemosphere, 2023)

Assessing oil price volatility co-movement with stock market volatility through quantile regression approach - Fang Liu; Muhammad Umair; Junjun Gao (Resources Policy, 2023)

Ridge intertillage alters rhizosphere bacterial communities and plant physiology to reduce yield loss of waterlogged cotton - Yanjun Zhang; Shizhen Xu; Guangya Liu; Tengxiang Lian; Zhenhuai Li; Tiantian Liang; Dongmei Zhang; Zhengpeng Cui; Lijie Zhan; Lin Sun; Junjun Nie; Jianlong Dai; et al. (Field Crops Research, 2023)

Computational identification and systematic classification of cytochrome P450 genes in Pogostemon cablin provide insights into flavonoids biosynthesis - Junjun Li; Cao Deng; Mengjia Liu; Yang He (Acta Physiologiae Plantarum, 2023)

Metagenomic analysis reveals patterns and hosts of antibiotic resistance in different pig farms - Bingzhen Ji; Junjun Qin; Yijia Ma; Xin Liu; Tian Wang; Guiming Liu; Bugao Li; Guoliang wang; Pengfei Gao (Environmental Science and Pollution Research, 2023)

Preconceptional exposure of adult male rats to bisphenol S impairs insulin sensitivity and glucose tolerance in their male offspring - Pengfei Gong; Danielle Bailbé; Stefania Tolu; Gaëlle Pommier; Junjun Liu; Jamileh Movassat (Chemosphere, 2023)

Diverse lignans with protective effect against hypoxia/oxidative injuries to H9c2 cells from Syringa pinnatifolia Hemsl. - Shungang Jiao; Xiaoli Gao; Junjun Li; Ruifei Zhang; Shana Wuken; Changxin Liu; Suyile Chen; Pengfei Tu; Luqi Huang; Xingyun Chai (Phytochemistry, 2023)

Response of partial nitritation/anammox granules to biodegradable organic input in bacterial community and functions - Feiyue Qian; Yaru Liu; Chenyun Mo; Huan Zhang; Feng Yan; Junjun Gao; Jinlong Zhuang (Journal of Water Process Engineering, 2023)

Effects of fine ambient particulate matters on de novo hypertensive disorders of pregnancy and blood pressure before 20 weeks - Zhichao Yuan; Qin Li; Tao Su; Jie Yang; Junjun Chen; Yuanzhou Peng; Shuang Zhou; Heling Bao; Shusheng Luo; Hui Wang; Jue Liu; Na Han; et al. (Environmental Research, 2023)

Vertical distribution of PbI2 nanosheets for robust air-processed perovskite solar cells - Zhenkun Zhu; Jitao Shang; Guanqi Tang; Zhen Wang; Xiaxia Cui; Junjun Jin; Yuan Zhou; Xiang Zhang; Dan Zhang; Xiaowei Liu; Qidong Tai (Chemical Engineering Journal, 2023)

Rainfall interception measurements and modeling in a semiarid evergreen spruce (Picea crassifolia) forest - Junjun Yang; Zhibin He; Jianmin Feng; Pengfei Lin; Jun Du; Lingxia Guo; Yufeng Liu; Jialiang Yan (Agricultural and Forest Meteorology, 2023)

Impacts of regional uplift of the Tibetan Plateau on local summer precipitation and downstream moisture budget: A simulation study - Kai Yang; Jinghua Chen; Chunsong Lu; Junjun Li; Tianyu Liu; Liping Deng; Yanwei Li (International Journal of Climatology, 2022)
Using the Weather Research and Forecasting (WRF) model, a series of sensitivity experiments were conducted to study the individual and overall effects of the various topographic uplifts of the Tibetan Plateau (TP) on regional climate variability. The presence of the southern slope of the TP facilitates the maintenance and development of the South Asia High (SAH), which produces a positive cyclic response between local precipitation and SAH, so that the northern branch of the South Asian summer monsoon (SASM) maintains the water vapor supply. At the same time, the southern slope of the TP has a positive effect on the mid‐latitude tropospheric anomalous cyclone and anticyclone systems which promotes the downstream advancement of the East Asian summer monsoon (EASM) and is favourable for the transfer of water vapor and convective clouds downstream. The role of the TP platform is mainly due to the lifting of moisture generated by its local heating, which favours the formation of local convective clouds and precipitation while causing nonadiabatic warming of the troposphere. Water vapor transported from the TP could affect precipitation in central‐eastern China (CEC). However, the supply of water vapor in Southern East China (SEC) mainly comes from the southeast coast of China. The Tibetan Plateau sensitive areas (TPSA) have impacts on the water vapor transport path. Removing the TPSA favours an increase in precipitation and convective clouds in SEC. The removal of topographic disturbances favours the convergence and dispersion of water vapor at mid‐latitudes. The mid‐latitude dynamical anomaly may form a standoff with the low‐latitude dynamical system. This leads to inefficient precipitation and convective generation processes, a weakened monsoon advance over land, and a southward shift in the rainfall belt.

Relationships between Cloud Droplet Spectral Relative Dispersion and Entrainment Rate and Their Impacting Factors - Shi Luo; Chunsong Lu; Yangang Liu; Yaohui Li; Wenhua Gao; Yujun Qiu; Xiaoqi Xu; Junjun Li; Lei Zhu; Yuan Wang; Junjie Wu; Xinlin Yang (Advances in Atmospheric Sciences, 2022)

Association between plasminogen activator inhibitor-1 gene polymorphisms and susceptibility to Parkinson’s disease in Chinese patients - Qi Xu; Qilun Lai; Junjun Wang; Liying Zhuang; Lin Cheng; Yejia Mo; Lu Liu; Zexian Zhao; Ying Zhang; Shiting Weng; Song Qiao (Acta Neurologica Belgica, 2022)

Identifying Carbon-Degrading Enzyme Activities in Association with Soil Organic Carbon Accumulation Under Land-Use Changes - Junjun Wu; Xiaoli Cheng; Yiqi Luo; Wenzhi Liu; Guihua Liu (Ecosystems, 2022)

Distinctive Roles of Wnt Signaling in Chondrogenic Differentiation of BMSCs under Coupling of Pressure and Platelet-Rich Fibrin - Baixiang Cheng; Fan Feng; Fan Shi; Jinmei Huang; Songbai Zhang; Yue Quan; Teng Tu; Yanli Liu; Junjun Wang; Ying Zhao; Min Zhang (Tissue Engineering and Regenerative Medicine, 2022)

Euler solution selecting method based on the damping factor - Liu Qiang; Yao Changli; Luo Yao; Yang Junjun; Li Zelin (Acta Geophysica, 2022)

Modeling, Control and Experiments of a Novel Underwater Vehicle with Dual Operating Modes for Oceanographic Observation - Junjun Cao; Rui Lin; Baoheng Yao; Chunhu Liu; Xiaochao Zhang; Lian Lian (Journal of Marine Science and Engineering, 2022)
Multifarious and continuous oceanographic observation data is of considerable significance to oceanographic research and military application. In this paper, a novel oceanographic observation method with dual-modal underwater vehicle able to switch between the Argo and Glider modes is proposed and is studied experimentally in the South China Sea. Using the Newton–Euler formulation, a complete dynamic model considering the variation in gravity/buoyancy due to mode switching is thus established. Then, based on Lyapunov stability criterion, a nonlinear adaptive inverse controller with multiple inputs and multiple outputs is developed which enables the observation platform to freely switch between various modes. By analyzing the numerical and experimental data of a single mode, the results demonstrate that the proposed method can supplement the observation data and improve the accuracy of oceanographic data. Finally, based on experimental data acquired by the dual-modal underwater vehicle in the South China Sea, three-dimensional regional oceanic temperature and salinity fields are constructed with the spatio-temporal Kriging method, and feature surfaces are extracted from the oceanic fields. Furthermore, the proposed method can be applied in other stirring dynamic regions, such as ocean eddies, ocean fronts, filaments, etc.

Selenium Ameliorates S. aureus-Induced Inflammation in Bovine Mammary Epithelial Cells by Regulating ROS-Induced NLRP3 Inflammasome - Yan Yang; Shenjin Lv; Zhennan Wang; Junjun Liu (Biological Trace Element Research, 2022)

Sevoflurane-Induced Neurotoxicity in the Developing Hippocampus via HIPK2/AKT/mTOR Signaling - Lirong Liang; Ze Fan; Danyi He; Youyi Zhao; Tian Zeng; Bing Liu; Tianyuan Ma; Junjun Kang; Hui Zhang (Neurotoxicity Research, 2022)

Characterization and Phylogenetic Analysis of the Complete Mitochondrial Genome of Saturnia japonica - Jiang Liu; Junjun Dai; Jinjin Jia; Yemei Zong; Yahao Sun; Ying Peng; Lei Wang; Cen Qian; Baojian Zhu; Guoqing Wei (Biochemical Genetics, 2022)

Dynamic Appointment Rescheduling of Trucks under Uncertainty of Arrival Time - Bowei Xu; Xiaoyan Liu; Junjun Li; Yongsheng Yang; Junfeng Wu; Yi Shen; Ye Zhou (Journal of Marine Science and Engineering, 2022)
The uncertainty of the arrival time of trucks has increased the complexity of terminal operations. The truck appointment system (TAS) cannot respond to this problem in time, which can easily cause appointment invalidation and reduce the efficiency of truck operations and terminal operations. This paper comprehensively considers the related constraints of truck re-scheduling costs, gate waiting costs, and idle emission costs. With the goal of minimizing the comprehensive operating costs of truck companies and port companies, a dynamic appointment rescheduling model for external trucks based on mixed integer nonlinear programming is established. This paper designs an adaptive quantum revolving door update mechanism and proposes a double-chain real quantum genetic algorithm. The simulation experiment results show that compared with the traditional scheduling, the truck dynamic appointment rescheduling model can effectively reduce the comprehensive operating costs of the truck company and the port company and alleviate the congestion of the port. The probability that the truck cannot arrive at the port on time, the advance time for the truck to confirm the arrival time, and the length of time that the external truck cannot arrive at the port on time have a significant impact on the cost of the reschedule of the TAS. This paper favorably supports the manager’s operational decision-making.

Application of a two-step sampling strategy based on deep neural network for landslide susceptibility mapping - Jingyu Yao; Shengwu Qin; Shuangshuang Qiao; Xiaowei Liu; Lingshuai Zhang; Junjun Chen (Bulletin of Engineering Geology and the Environment, 2022)

A new abietane-type diterpenoid and a new long-chain alkenone from fungus Daldinia sp. TJ403-LS1 - Shuang Lin; Xueke Zhang; Ling Shen; Shuyuan Mo; Junjun Liu; Jianping Wang; Zhengxi Hu; Yonghui Zhang (Natural Product Research, 2022)

Genetic dissection of quantitative trait loci for grain size and weight by high-resolution genetic mapping in bread wheat (Triticum aestivum L.) - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Juanyu Zhang; Xvebing Qiu; Xi Pu; Wuyun Yang; Jun Li; Zehou Liu; et al. (Theoretical and Applied Genetics, 2022)

Differential Expression and Distinct Roles of Proteinase-Activated Receptor 2 in Microglia and Neurons in Neonatal Mouse Brain After Hypoxia-Ischemic Injury - Yicong Liu; Hui Li; Jiangqi Hu; Zhou Wu; Jie Meng; Yoshinori Hayashi; Hiroshi Nakanishi; Hong Qing; Junjun Ni (Molecular Neurobiology, 2022)

Effects of Acid Sulfate and Chloride Ion on the Pore Structure and Mechanical Properties of Sandstone Under Dynamic Loading - Xiaoliang Li; Zhentang Liu; Xiaojun Feng; Huajie Zhang; Junjun Feng (Rock Mechanics and Rock Engineering, 2021)

Identification and validation of two major QTLs for spike compactness and length in bread wheat (Triticum aestivum L.) showing pleiotropic effects on yield-related traits - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Xvebing Qiu; Xi Pu; Jun Li; Zehou Liu; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

Substances for regenerative wound healing during antler renewal stimulated scar-less restoration of rat cutaneous wounds - Qianqian Guo; Zhen Liu; Junjun Zheng; Haiping Zhao; Chunyi Li (Cell and Tissue Research, 2021)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

Nrf2 deficiency aggravates the kidney injury induced by subacute cadmium exposure in mice - Chengjie Chen; Xue Han; Gang Wang; Dan Liu; Lina Bao; Congcong Jiao; Junjun Luan; Yongyong Hou; Yuanyuan Xu; Huihui Wang; Qiang Zhang; Hua Zhou; et al. (Archives of Toxicology, 2021)

QTL mapping for foxtail millet plant height in multi-environment using an ultra-high density bin map - Qiang He; Hui Zhi; Sha Tang; Lu Xing; Suying Wang; Haigang Wang; Aiying Zhang; Yuhui Li; Ming Gao; Haijin Zhang; Guoqiu Chen; Shutao Dai; et al. (Theoretical and Applied Genetics, 2021)

Synthesis of 4-oxotetrahydropyrimidine-1(2H)-carboxamides derivatives as capsid assembly modulators of hepatitis B virus - Nicky Hwang; Haiqun Ban; Junjun Chen; Julia Ma; Hui Liu; Patrick Lam; John Kulp; Stephan Menne; Jinhong Chang; Ju-Tao Guo; Yanming Du (Medicinal Chemistry Research, 2021)

Astragaloside protects rat brain from microwave-induced functional injuries via restoring acetylcholine and normalizing electroencephalogram - Li Zhao; Yunbo Sun; Chao Yu; Junjun Chen; Xinping Xu; Xueyan Zhang; Hui Wang; Jing Zhang; Haoyu Wang; Ji Dong; Binwei Yao; Hongmei Zhou; et al. (Environmental Science and Pollution Research, 2020)

Asymmetric response of soil methane uptake rate to land degradation and restoration: Data synthesis - Junjun Wu; Qiong Chen; Wei Jia; Chunyan Long; Wenzhi Liu; Guihua Liu; Xiaoli Cheng (Global Change Biology, 2020)
Land degradation and restoration profoundly affect soil CH 4 uptake capacity in terrestrial ecosystems. However, a comprehensive assessment of the response of soil CH 4 uptake to land degradation and restoration at global scale is not available. Here, we present a global meta‐analysis with a database of 228 observations from 83 studies to investigate the effects of land degradation and restoration on the capacity of soil CH 4 uptake. We found that land degradation significantly decreased the capacity of soil CH 4 uptake, except the conversion of pasture to cropland where the soil CH 4 uptake rate showed no response. In contrast, all types of land restoration significantly increased the capacity of soil CH 4 uptake. Interestingly, the response of soil CH 4 uptake rate to land degradation and restoration was asymmetric: the increased soil CH 4 uptake rate in response to the land restoration was smaller compared to the decrease in CH 4 uptake rate induced by the land degradation. The effect of land degradation on soil CH 4 uptake rate was not dependent on the time since land use change, but the CH 4 sink strength increased with the time since land restoration. The response of soil CH 4 uptake rate to both land degradation and restoration was predominantly regulated by changes in the soil water‐filled pore space, soil bulk density, and pH, whereas alterations in the substrate quantity and quality had negligible effect. Additionally, the effects of land degradation and restoration on soil CH 4 uptake were strongly related to the mean annual precipitation and soil texture. Overall, our results provide novel insights for understanding of how land degradation and restoration can affect the CH 4 sink strength of upland soils, and more importantly, our findings are beneficial to take measures to enhance the potential of soil CH 4 uptake in response to global land use change.

Permeability-enhanced rate model for coal permeability evolution and its application under various triaxial stress conditions - Jing Xie; Mingzhong Gao; Junjun Liu; Cong Li; Gaoyou Peng (Arabian Journal of Geosciences, 2020)

The miR-15/16 Cluster Is Involved in the Regulation of Vertebrate LC-PUFA Biosynthesis by Targeting pparγ as Demonostrated in Rabbitfish Siganus canaliculatus - Junjun Sun; Cuiying Chen; Cuihong You; Yang Liu; Hongyu Ma; Óscar Monroig; Douglas R. Tocher; Shuqi Wang; Yuanyou Li (Marine Biotechnology, 2020)

Reporter gene knock-in into Marc-145 cells using CRISPR/Cas9-mediated homologous recombination - Yanyan Chang; Junjun Shao; Yuan Gao; Wei Liu; Zhan Gao; Yonghao Hu; Huiyun Chang (Biotechnology Letters, 2020)

Development of Simple Sequence Repeat Markers from De Novo Assembled Transcriptomes of Pumpkins - Qiusheng Kong; Yong Liu; Junjun Xie; Zhilong Bie (Plant Molecular Biology Reporter, 2020)

Membrane proteomic analysis reveals the intestinal development is deteriorated by intrauterine growth restriction in piglets - Shimeng Huang; Cong Liu; Na Li; Zhenhua Wu; Tiantian Li; Dandan Han; Zhen Li; Jiangchao Zhao; Junjun Wang (Functional & Integrative Genomics, 2020)

Nitric oxide mediates aluminum-induced citrate secretion through regulating the metabolism and transport of citrate in soybean roots - Huahua Wang; Yangyang Zhang; Junjie Hou; Wenwen Liu; Junjun Huang; Weihong Liang (Plant and Soil, 2019)

Characterization of extracellular polysaccharide/protein contents during the adsorption of Cd(II) by Synechocystis sp. PCC6803 - Li Shen; Zhanfei Li; Junjun Wang; Ajuan Liu; Zhenhua Li; Runlan Yu; Xueling Wu; Yuandong Liu; Jiaokun Li; Weimin Zeng (Environmental Science and Pollution Research, 2018)

Microbial fuel cells coupling with the three-dimensional electro-Fenton technique enhances the degradation of methyl orange in the wastewater - Tao Huang; Longfei Liu; Junjun Tao; Lulu Zhou; Shuwen Zhang (Environmental Science and Pollution Research, 2018)

Mapping soil organic carbon stocks of northeastern China using expert knowledge and GIS-based methods - Xiaodong Song; Feng Liu; Bing Ju; Junjun Zhi; Decheng Li; Yuguo Zhao; Ganlin Zhang (Chinese Geographical Science, 2017)

Secreted expression of truncated capsid protein from porcine circovirus type 2 in Pichia pastoris - Xiaohong Chen; Junjun Chen; Yuanxing Zhang; Ping Zhu; Yong Deng; Qin Liu (Biotechnology Letters, 2016)

Comparative analysis of genetic structure in Magnaporthe oryzae isolates from indica and japonica hosts in China - Junjun Shang; Yina Wang; Liu Su; Mansi Luo; Xin Yan; Chao Yu; Youlin Zhu (Journal of General Plant Pathology, 2016)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Effects of Different Sources and Levels of Copper on Growth Performance, Nutrient Digestibility, and Elemental Balance in Young Female Mink (Mustela vison) - Xuezhuang Wu; Tietao Zhang; Zhi Liu; Junjun Zheng; Jungang Guo; Fuhe Yang; Xiuhua Gao (Biological Trace Element Research, 2014)

Amino acids modulates the intestinal proteome associated with immune and stress response in weaning pig - Man Ren; Chuang Liu; Xiangfang Zeng; Longyao Yue; Xiangbing Mao; Shiyan Qiao; Junjun Wang (Molecular Biology Reports, 2014)

Heterologous expression and characterization of a malathion-hydrolyzing carboxylesterase from a thermophilic bacterium, Alicyclobacillus tengchongensis - Zhenrong Xie; Bo Xu; Junmei Ding; Lingyun Liu; Xuelin Zhang; Junjun Li; Zunxi Huang (Biotechnology Letters, 2013)

Preliminary genetic linkage maps of Chinese herb Dendrobium nobile and D. moniliforme - SHANGGUO FENG; HONGYAN ZHAO; JIANGJIE LU; JUNJUN LIU; BO SHEN; HUIZHONG WANG (Journal of Genetics, 2013)

PotD protein stimulates biofilm formation by Escherichia coli - Xiao Zhang; Yuzhen Zhang; Junjun Liu; Honglei Liu (Biotechnology Letters, 2013)

Associations Between EEG Beta Power Abnormality and Diagnosis in Cognitive Impairment Post Cerebral Infarcts - Yanping Wang; Xiaoling Zhang; Junjun Huang; Minchu Zhu; Qiaobing Guan; Chunfeng Liu (Journal of Molecular Neuroscience, 2013)

Molecular cloning and characterization of a tropinone reductase from Dendrobium nobile Lindl - Wei Chen; Xiaofei Cheng; Zhenhua Zhou; Junjun Liu; Huizhong Wang (Molecular Biology Reports, 2013)

Determination of GABAAα1 and GABAB1 receptor subunits expression in tissues of gilts during the late gestation - Zhiyong Fan; Yonghui Chen; Junjun Wang; Jinping Deng; Dexing Hou; Tiejun Li; Lingyuan Yang; Zhonghua Liu; Xiaosong Wu (Molecular Biology Reports, 2013)

Enzymatic synthesis of β-N-(γ-l(+)-glutamyl)phenylhydrazine with Escherichia coli γ-glutamyltranspeptidase - Hongjuan Zhang; Yueping Zhan; Junjun Chang; Junzhong Liu; Lisheng Xu; Zhiyuan Wang; Qian Liu; Qingcai Jiao (Biotechnology Letters, 2012)

Application of land-use change model in guiding regional planning: A case study in Hun-Taizi River Watershed, Northeast China - Miao Liu; Yuanman Hu; Wei Zhang; Junjun Zhu; Hongwei Chen; Fengming Xi (Chinese Geographical Science, 2011)

A 796 bp PsPR10 gene promoter fragment increased root-specific expression of the GUS reporter gene under the abiotic stresses and signal molecules in tobacco - Xiangbin Xu; Sai Guo; Kai Chen; Hongmiao Song; Junjun Liu; Longbiao Guo; Qian Qian; Huizhong Wang (Biotechnology Letters, 2010)

Eco-toxic effects of sulfadiazine sodium, sulfamonomethoxine sodium and enrofloxacin on wheat, Chinese cabbage and tomato - Caixia Jin; Qiuying Chen; Ruilian Sun; Qingxiang Zhou; Junjun Liu (Ecotoxicology, 2009)

Homologous-Restraint Polymerase Chain Reaction: An Efficient and Rapid Protocol to Clone Multiple Homologous Genes - Ming Chen; Honglei Liu; Yunfeng Bai; Zhenghong Zhang; Junjun Liu; Yuzhen Zhang (Current Microbiology, 2008)

Complete nucleotide sequence of a Chinese serotype Asia1 vaccine strain of foot-and-mouth disease virus - Junzheng Du; Huiyun Chang; Guozheng Cong; Junjun Shao; Tong Lin; Youjun Shang; Zaixin Liu; Xiangtao Liu; Xuepeng Cai; Qingge Xie (Virus Genes, 2007)

Design and Structure--Activity Relationship of Novel Endothelin Receptor A Tripeptide Antagonists - Junjun Dong; Ning Yang; Yuanjun Liang; Ping Wu; Xin Li; Keliang Liu (International Journal of Peptide Research and Therapeutics, 2005)